복숭아 품종별 액상복숭아청의 품질 특성 - 정경미(Kyung-Mi Jung); 김영준(Young-Jun Kim); 이기우(Gi-Woo Lee); 권오흔(Oh-Heun Kwon) (동아시아식생활학회지, 2017)
This study was conducted to investigate the quality characteristics of sugar-preserved peach juice manufactured using concentrates of various peach cultivars (NT: non-added peach concentrates, KC: Kanabam white peach, CC: Chunhong, JC: Janghowon Hwangdo, MC: mixed cultivar (KC+CC+JC)). The sugar content of sugar-preserved peach juice increased by 5 °Bx relative to NT, and the total acid contents of CC and MC were found to be 1.14±0.02% and 1.02±0.02%, respectively, which were significantly higher than those of other experimental groups. The contents of free fructose and glucose of KC and CC were significantly higher than other groups, while the levels of sucrose and maltose in CC were not detected. The lowest citric acid content and the highest acetic acid content were observed in JC while CC showed the highest citric acid content and the lowest acetic acid and tartaric acid content. In general, the nutritional components of the MC group were improved. The antioxidant activity, total phenol and total flavonoid contents were found to be significantly high in the CC and MC process areas. Overall, the sugar-preserved peach juice manufactured using peach concentrates showed improved quality characteristics and antioxidant activity. Specifically, MC had similar or better quality characteristics than juice prepared from individual peach concentrates. KCI Citation Count: 3